A Bout of High-Intensity Interval Training Increases Seric Musclin in Adults with Metabolic Syndrome (2018)
ABSTRACT: Musclin is a myokine which induces insulin resistance (IR) in vitro, also proposed to favor aerobic capacity in murine models, which seems contradictory. Because of that, and since exercise contributes to improve IR in metabolic syndrome (MS) probably by regulating myokines, it is necessary to understand exercise´s role in regulating musclin in humans